Dual chamber pacing in obstructive hypertrophic cardiomyopathy. Preliminary information - Jesús Castro Hevia; Yanela Fayad Rodríguez; Francisco Dorticós Balea; Roberto Zayas Molina; Raúl Díaz Padrón Camejo; Juan Prohías Martínez; Angela Castro Arca (ECIMED, 2014)
Dual chamber pacing in patients suffering from obstructive hypertrophic cardiomyopathy reduces subatrial pressure gradient and improves symptoms. In two years, 8 patients (4 women and 4 men) aged 15-19 years old (average 40) were trated and studied; they showed subatrial gradients equal to or higher than 54 mmHg according to echocardiography results by adding 20 mmKg to peak gradient of mitral valve failure and substracting the same from systolic pressure detemined by shygmomanometry. All patients kept II-IV grade functional capacity as indicated in NYHA classification in spite of the drug therapy with maximum tolerable dosage of beta-blockers and anticalcic drugs. They were implanted dual-chamber pacers with 100 mseg AV delay programming which was modified according to the evolution of echocardiographic & clinical results. The average subatrial pressure gradient was 78 mmHg before pacer implanting and 31 mmHg after a follow-up period from 1.5 to 21 months in wich pressure gradients were reduced by 60 % and patients reached I-II grade functional capacity. This method is an alternative for those patients who do not improve their condition with drug therapy before deciding to treat them surgically. Nevertheless, obstruction is just one part of the complex pathology of this disease since diastolic dysfunction, myocardial ischemia and arrhythmias are other disorders where the effects of pacer treatment is not yet defined.